Occlusion type lap joint double-waterproof-layer prefabricated polymer waterproof coiled material
By using a bite -type overlap dual -road waterproof layer structure in the waterproof coil material and the complex method of adding Mao metal polyethylene and calcium -zinc stabilizers, the problem of poor mechanical performance and aging resistance of traditional waterproof coils has been solved. High waterproof performance and longer service life.
Patent Information
- Application Number
- CN202411494355.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-10-24
AI Technical Summary
Traditional asphalt waterproof coils have poor mechanical properties and are prone to cracking and aging during long-term use, resulting in poor waterproofing performance of buildings and affecting the service life and safety of buildings.
The prefabricated polymer waterproof membrane with an overlapping dual-layer waterproof layer is used. A layered overlapping edge structure is set on one side of the membrane, and the overlapping method is used to enhance the tensile strength and shear resistance of the overlap. At the same time, metallocene polyethylene and calcium zinc stabilizer are added to the waterproof layer to improve the mechanical properties and aging resistance of the waterproof membrane.
It improves the mechanical properties and aging resistance of waterproof membranes, enhances waterproof performance, solves the problems of easy cracking and aging of traditional waterproof membranes, and reduces building maintenance costs.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of waterproof materials, and in particular to a prefabricated polymer waterproof coiled material with a bite-type overlapping double-channel waterproof layer. Background Art
[0002] With the acceleration of urbanization and the continuous improvement of people's requirements for the quality of residential and public buildings, the importance of building waterproofing has become increasingly prominent. During the use of buildings, they are eroded by rainwater, groundwater, domestic water, etc. If the waterproofing measures are not in place, it is easy to cause leakage problems, which not only affects the beauty and use function of the building, but also may shorten the service life of the building and even threaten the safety of the building structure. Waterproof membranes have been widely used in the field of building waterproofing due to their excellent performance. However, traditional asphalt waterproof membranes have poor mechanical properties and are prone to cracking and aging during long-term use. Therefore, it is necessary to develop a waterproof membrane with good mechanical properties and aging resistance to enhance the durability of the waterproof membrane and reduce the maintenance cost of the building. Summary of the invention
[0003] The invention provides a prefabricated polymer waterproofing coiled material with a double waterproof layer of occlusal overlap, which solves the problem of poor mechanical properties and aging resistance of the waterproofing coiled material in the related art.
[0004] The technical solution of the present invention is as follows: The present invention provides a prefabricated polymer waterproofing roll material with a double-layer overlapping waterproofing layer, wherein the polymer waterproofing roll material comprises a first waterproofing layer, a base layer, and a second waterproofing layer from top to bottom; One side of the polymer waterproof roll is provided with an overlapping opening, which is formed by separating the first waterproof layer and the second waterproof layer from each other and is used for interlocking overlapping with a side of another polymer waterproof roll without an overlapping opening.
[0005] On one of the long sides of the coiled material in the long side direction, the first waterproof layer and the second waterproof layer are separated from each other to form a layered overlapping edge structure; and the composite integral edge of another coiled material is overlapped in a bite-type manner; The first waterproof layer and the second waterproof layer each independently include the following raw materials in parts by weight: 85-95 parts of PVC resin, 15-30 parts of metallocene polyethylene, 45-55 parts of plasticizer, 18-22 parts of filler, 1-5 parts of calcium zinc stabilizer, 1-2 parts of antioxidant, 5-8 parts of talc, 3-5 parts of titanium dioxide, and 2-3 parts of compatibilizer.
[0006] As a further technical solution, the mass ratio of the metallocene polyethylene to the calcium zinc stabilizer is 5~11:1.
[0007] In the present invention, the mechanical properties and aging resistance of the waterproof coiled material are further improved by limiting the mass ratio of the metallocene polyethylene to the calcium zinc stabilizer to 5-11:1.
[0008] As a further technical solution, the metallocene polyethylene includes a first metallocene polyethylene and a second metallocene polyethylene, and the first metallocene polyethylene and the second metallocene polyethylene have different melt indexes.
[0009] As a further technical solution, the melt index of the first metallocene polyethylene is 0.8 g / 10 min (190° C. / 2.16 kg), and the melt index of the second metallocene polyethylene is 3.5 g / 10 min (190° C. / 2.16 kg).
[0010] As a further technical solution, the mass ratio of the first metallocene polyethylene to the second metallocene polyethylene is 5-7:1.
[0011] In the present invention, by limiting the mass ratio of the first metallocene polyethylene to the second metallocene polyethylene to 5-7:1, the mechanical properties and aging resistance of the waterproof coiled material are further improved.
[0012] As a further technical solution, the filler is calcium carbonate modified by a modifier, and the modifier includes a silane coupling agent and 2-aminophenol-4-sulfonylureamid.
[0013] In the present invention, the calcium carbonate is modified by using a silane coupling agent and 2-aminophenol-4-sulfonylureamid, thereby further improving the mechanical properties and aging resistance of the waterproof coiled material.
[0014] As a further technical solution, the preparation method of the filler includes the following steps: dissolving a silane coupling agent and 2-aminophenol-4-sulfonylureamid in an acidic aqueous solution, adding calcium carbonate for modification, and obtaining the filler after filtering and drying.
[0015] As a further technical solution, the modification temperature is 50° C. and the modification time is 6 hours.
[0016] As a further technical solution, the silane coupling agent is γ-methacryloxypropyl-trimethoxysilane.
[0017] As a further technical solution, the acidic aqueous solution is a hydrochloric acid aqueous solution.
[0018] As a further technical solution, the pH of the hydrochloric acid aqueous solution is 4-6.
[0019] As a further technical solution, the amount of the modifier added is 2% to 5% of the mass of the calcium carbonate.
[0020] As a further technical solution, the mass ratio of the silane coupling agent to the 2-aminophenol-4-sulfonylureamid is 4-7:1.
[0021] As a further technical solution, the antioxidant includes one or more of antioxidant 1010, antioxidant 168, and antioxidant DLTP.
[0022] As a further technical solution, the compatibilizer includes one or two of maleic anhydride grafted polyethylene and maleic anhydride grafted polypropylene.
[0023] As a further technical solution, the tire base layer is glass fiber cloth.
[0024] As a further technical solution, the plasticizer is plasticizer DOTP.
[0025] As a further technical solution, the thickness of the first waterproof layer and the second waterproof layer are independently 1.2 mm to 1.5 mm.
[0026] The present invention also provides a method for preparing a prefabricated polymer waterproofing membrane with a double-layer waterproofing layer of a bite-type overlap, comprising the following steps: S1, melt-extrude the first waterproof layer raw material and the second waterproof layer raw material respectively, and then calender to obtain the first waterproof layer sheet and the second waterproof layer sheet; S2. Lay the first waterproof layer sheet and the second waterproof layer sheet on both sides of the base layer respectively, and obtain the bite-type overlapping double-layer waterproof prefabricated polymer waterproof membrane after hot pressing.
[0027] The present invention also proposes a construction process for the prefabricated polymer waterproofing membrane with a double-layer waterproofing layer of the bite-type overlap, which comprises the following steps: The first polymer waterproof membrane is laid on the base layer according to the design requirements. The first polymer waterproof membrane is provided with a first waterproof layer and a second waterproof layer on one side of the overlapping opening, which are overlapped on the first waterproof layer and the second waterproof layer on the non-overlapping opening side of the other polymer waterproof membrane respectively, and hot air welded to form an interlocking overlapping structure.
[0028] The working principle and beneficial effects of the present invention are: In the present invention, by arranging a layered overlapping edge structure on one side of the waterproof coiled material and adopting a bite overlapping method, the tensile strength and shear strength of the overlapping joint are enhanced, water vapor penetration is blocked, and the waterproof performance is improved; by adding metallocene polyethylene and calcium zinc stabilizer to the waterproof layer for compounding, the mechanical properties and aging resistance of the waterproof coiled material are improved, and the problem of poor mechanical properties and aging resistance of the waterproof coiled material is solved. DETAILED DESCRIPTION
[0029] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] In the following examples and comparative examples: Metallocene polyethylene model NG 5045.11P, melt index (190°C, 2.16kg): 0.8g / 10min; Metallocene polyethylene model 3518CB, melt index (190°C, 2.16kg): 3.5g / 10min; PVC resin, model: P440; calcium zinc stabilizer, model GP382, purchased from Qingdao Guangde New Materials Co., Ltd.; Maleic anhydride grafted polyethylene, model: AT1113A; Maleic anhydride grafted polypropylene, model: P613.
[0031] Example 1 A method for preparing a prefabricated polymer waterproofing membrane with a double-layer waterproofing layer of a bite-type overlap, comprising the following steps: S1, melt-extrude 85 parts of PVC resin, 19 parts of metallocene polyethylene 3518CB, 45 parts of plasticizer DOTP, 18 parts of calcium carbonate, 5 parts of calcium zinc stabilizer, 1 part of antioxidant 1010, 5 parts of talc, 3 parts of titanium dioxide, and 2 parts of maleic anhydride grafted polyethylene, and calender to obtain a first waterproof layer sheet with a thickness of 1.2 mm; S2, 85 parts of PVC resin, 19 parts of metallocene polyethylene 3518CB, 45 parts of plasticizer DOTP, 18 parts of calcium carbonate, 5 parts of calcium zinc stabilizer, 1 part of antioxidant 1010, 5 parts of talc, 3 parts of titanium dioxide, and 2 parts of maleic anhydride grafted polyethylene were melt-extruded, and then calendered to obtain a second waterproof layer sheet with a thickness of 1.2 mm; S3, laying the first waterproof layer sheet and the second waterproof layer sheet on both sides of the glass fiber cloth respectively, and obtaining the bite-type overlapping double-layer waterproof prefabricated polymer waterproof membrane after hot pressing.
[0032] Example 2 A method for preparing a prefabricated polymer waterproofing membrane with a double-layer waterproofing layer of a bite-type overlap, comprising the following steps: S1, melt-extrude 90 parts of PVC resin, 15 parts of metallocene polyethylene 3518CB, 50 parts of plasticizer DOTP, 20 parts of calcium carbonate, 4 parts of calcium zinc stabilizer, 1 part of antioxidant 168, 7 parts of talc, 4 parts of titanium dioxide, and 3 parts of maleic anhydride grafted polypropylene, and calender to obtain a first waterproof layer sheet with a thickness of 1.3 mm; S2, melt-extrude 90 parts of PVC resin, 15 parts of metallocene polyethylene 3518CB, 50 parts of plasticizer DOTP, 20 parts of calcium carbonate, 4 parts of calcium zinc stabilizer, 1 part of antioxidant 168, 7 parts of talc, 4 parts of titanium dioxide, and 3 parts of maleic anhydride grafted polypropylene, and calender to obtain a second waterproof layer sheet with a thickness of 1.3 mm; S3, laying the first waterproof layer sheet and the second waterproof layer sheet on both sides of the glass fiber cloth respectively, and obtaining the bite-type overlapping double-layer waterproof prefabricated polymer waterproof membrane after hot pressing.
[0033] Example 3 A method for preparing a prefabricated polymer waterproofing membrane with a double-layer waterproofing layer of a bite-type overlap, comprising the following steps: S1, melt-extrude 95 parts of PVC resin, 30 parts of metallocene polyethylene 3518CB, 55 parts of plasticizer DOTP, 22 parts of calcium carbonate, 1 part of calcium zinc stabilizer, 2 parts of antioxidant DLTP, 8 parts of talc, 5 parts of titanium dioxide, and 3 parts of maleic anhydride grafted polypropylene, and calender to obtain a first waterproof layer sheet with a thickness of 1.5 mm; S2, melt-extrude 95 parts of PVC resin, 30 parts of metallocene polyethylene 3518CB, 55 parts of plasticizer DOTP, 22 parts of calcium carbonate, 1 part of calcium zinc stabilizer, 2 parts of antioxidant DLTP, 8 parts of talc, 5 parts of titanium dioxide, and 3 parts of maleic anhydride grafted polypropylene, and calender to obtain a second waterproof layer sheet with a thickness of 1.5 mm; S3, laying the first waterproof layer sheet and the second waterproof layer sheet on both sides of the glass fiber cloth respectively, and obtaining the bite-type overlapping double-layer waterproof prefabricated polymer waterproof membrane after hot pressing.
[0034] Example 4 The only difference between this embodiment and embodiment 1 is that the amount of metallocene polyethylene 3518CB added in S1 and S2 is 23 parts, and the amount of calcium zinc stabilizer added is 1 part.
[0035] Example 5 The only difference between this embodiment and embodiment 1 is that the amount of metallocene polyethylene 3518CB added in S1 and S2 is 20 parts, and the amount of calcium zinc stabilizer added is 4 parts.
[0036] Example 6 The only difference between this embodiment and embodiment 1 is that the amount of metallocene polyethylene 3518CB added in S1 and S2 is 22 parts, and the amount of calcium zinc stabilizer added is 2 parts.
[0037] Example 7 The only difference between this example and example 5 is that the metallocene polyethylene 3518CB in S1 and S2 is replaced by an equal amount of metallocene polyethylene NG 5045.11P.
[0038] Example 8 The only difference between this embodiment and embodiment 5 is that the metallocene polyethylene in S1 and S2 is composed of metallocene polyethylene NG 5045.11P and metallocene polyethylene 3518CB in a mass ratio of 5:1.
[0039] Example 9 The only difference between this embodiment and embodiment 5 is that the metallocene polyethylene in S1 and S2 is composed of metallocene polyethylene NG 5045.11P and metallocene polyethylene 3518CB in a mass ratio of 7:1.
[0040] Example 10 The only difference between this embodiment and embodiment 9 is that calcium carbonate is replaced by an equal amount of modified calcium carbonate.
[0041] Wherein, the preparation method of modified calcium carbonate comprises the following steps: 1.5 g of γ-methacryloyloxypropyl-trimethoxysilane and 0.5 g of 2-aminophenol-4-sulfonylethamide were dissolved in 300 mL of hydrochloric acid aqueous solution (pH 5), 40 g of calcium carbonate was added, and the mixture was stirred at 50° C. for 6 h. The modified calcium carbonate was obtained after filtration and drying.
[0042] Embodiment 11 The only difference between this embodiment and embodiment 10 is that the added amount of γ-methacryloxypropyl-trimethoxysilane is 1.8 g, and the added amount of 2-aminophenol-4-sulfonylureamid is 0.2 g.
[0043] Example 12 The only difference between this embodiment and embodiment 10 is that the added amount of γ-methacryloxypropyl-trimethoxysilane is 1.6 g, and the added amount of 2-aminophenol-4-sulfonylureamid is 0.4 g.
[0044] Example 13 The only difference between this embodiment and embodiment 10 is that the added amount of γ-methacryloxypropyl-trimethoxysilane is 1.75 g, and the added amount of 2-aminophenol-4-sulfonylureamid is 0.25 g.
[0045] Comparative Example 1 The only difference between this comparative example and Example 1 is that metallocene polyethylene 3518CB is not added.
[0046] Comparative Example 2 The only difference between this comparative example and Example 1 is that the calcium zinc stabilizer is replaced by stabilizer 770.
[0047] The waterproof membranes prepared in Examples 1 to 13 and Comparative Examples 1 to 2 were respectively measured for elongation at break according to Method B in GB / T 328.9-2007 "Test methods for building waterproof membranes Part 9: Tensile properties of polymer waterproof membranes"; Aging resistance: After the waterproof membrane is placed at 80°C for 168 hours, the change rate of its elongation at break is measured; Change rate of elongation at break = (1-elongation at break after heat aging / elongation at break before heat aging) × 100%; The test results are shown in Table 1.
[0048] Table 1 Waterproof membrane performance test results
[0049] Compared with Example 1, no metallocene polyethylene is added in Comparative Example 1, and the calcium zinc stabilizer is replaced with stabilizer 770 in Comparative Example 2. As a result, the elongation at break of the waterproof membrane prepared in Comparative Examples 1-2 is lower than that in Example 1, and the change rate of elongation at break after thermal aging is higher than that in Example 1, indicating that the addition of metallocene polyethylene and calcium zinc stabilizer to the waterproof membrane can improve the mechanical properties and aging resistance of the waterproof membrane.
[0050] Compared with Example 1, the mass ratio of metallocene polyethylene and calcium zinc stabilizer was changed in Examples 4 to 6. As a result, the elongation at break of the waterproof membrane prepared in Examples 5 to 6 was higher than that in Example 1 and Example 4, and the change rate of elongation at break after thermal aging was lower than that in Example 1 and Example 4, indicating that when the mass ratio of metallocene polyethylene and calcium zinc stabilizer is 5 to 11:1, the mechanical properties and aging resistance of the waterproof membrane can be further improved.
[0051] Compared with Example 5, Examples 7 to 9 change the composition of the metallocene polyethylene. As a result, the elongation at break of the waterproof membrane prepared in Examples 8 to 9 is higher than that in Example 5 and Example 7, and the change rate of elongation at break after thermal aging is lower than that in Example 5 and Example 7, indicating that when the mass ratio of the metallocene polyethylene with a melt index of 3.5 g / 10 min and the metallocene polyethylene with a melt index of 0.8 g / 10 min is 5 to 7:1, the mechanical properties and aging resistance of the waterproof membrane can be further improved.
[0052] Compared with Example 9, in Examples 10 to 13, silane coupling agent and 2-aminophenol-4-sulfonylureamid are used to modify calcium carbonate. As a result, the elongation at break of the waterproof membrane prepared in Examples 12 to 13 is higher than that in Examples 9, 10 and 11, and the change rate of elongation at break after thermal aging is lower than that in Examples 9, 10 and 11, indicating that when the mass ratio of silane coupling agent to 2-aminophenol-4-sulfonylureamid is 4 to 7:1, the mechanical properties and aging resistance of the waterproof membrane can be further improved.
[0053] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A prefabricated polymer waterproofing membrane with a double-layer occlusal overlap, characterized in that: The polymer waterproof coiled material comprises, from top to bottom, a first waterproof layer, a base layer, and a second waterproof layer; The first waterproof layer and the second waterproof layer each independently include the following raw materials in parts by weight: 85-95 parts of PVC resin, 15-30 parts of metallocene polyethylene, 45-55 parts of plasticizer, 18-22 parts of filler, 1-5 parts of calcium zinc stabilizer, 1-2 parts of antioxidant, 5-8 parts of talc, 3-5 parts of titanium dioxide, and 2-3 parts of compatibilizer.
2. The prefabricated polymer waterproofing membrane with double overlapping waterproof layers according to claim 1 is characterized in that: The mass ratio of the metallocene polyethylene to the calcium zinc stabilizer is 5-11:
1.
3. The prefabricated polymer waterproofing membrane with double overlapping waterproof layers according to claim 1 is characterized in that: The metallocene polyethylene includes a first metallocene polyethylene and a second metallocene polyethylene, and the first metallocene polyethylene and the second metallocene polyethylene have different melt indexes.
4. The prefabricated polymer waterproofing membrane with double overlapping waterproof layers according to claim 3 is characterized in that: The melt index of the first metallocene polyethylene is 0.8 g / 10 min (190° C. / 2.16 kg), and the melt index of the second metallocene polyethylene is 3.5 g / 10 min (190° C. / 2.16 kg).
5. The prefabricated polymer waterproofing membrane with double overlapping waterproof layers according to claim 4 is characterized in that: The mass ratio of the first metallocene polyethylene to the second metallocene polyethylene is 5-7:
1.
6. The prefabricated polymer waterproofing membrane with double overlapping waterproof layers according to claim 1 is characterized in that: The filler is obtained by modifying calcium carbonate with a modifier, and the modifier includes a silane coupling agent and 2-aminophenol-4-sulfonylureamid.
7. The prefabricated polymer waterproofing membrane with double overlapping waterproof layers according to claim 6 is characterized in that: The amount of the modifier added is 2% to 5% of the mass of the calcium carbonate.
8. The prefabricated polymer waterproofing membrane with double overlapping waterproof layers according to claim 6 is characterized in that: The mass ratio of the silane coupling agent to the 2-aminophenol-4-sulfonylureamid is 4-7:
1.
9. The prefabricated polymer waterproofing membrane with double overlapping waterproof layers according to claim 1, characterized in that: The antioxidant includes one or more of antioxidant 1010, antioxidant 168, and antioxidant DLTP.
10. The prefabricated polymer waterproofing membrane with double overlapping waterproof layers according to claim 1, characterized in that: The compatibilizer includes one or two of maleic anhydride grafted polyethylene and maleic anhydride grafted polypropylene.
Citation Information
Patent Citations
Radiation-proof and flame retardant PVC polymer waterproofing membrane and preparation method thereof
CN107501785A
Phthalimide modified room-temperature vulcanized fireproof silicone rubber and preparation method thereof
CN111393857A
Composite waterproof roll
CN114045120A
Preparation method of polyamino silane coupling agent modified antioxidant and silicon dioxide loaded
CN115197588A
Flexible low-temperature-resistant waterproof material and production method thereof
CN115991914A